(untitled) (Eurasian Journal of Ecology, 2016)
Work is devoted to complex research of an industrial zone of the former Aktyubinsk Chemical Plant (ACP) of S.M.Kirov and development of ways of decrease in risk for objects of environment and population health. Complex field and laboratory researches of level of pollution of the soil were conducted, the spatial characteristic of distribution of polluting substances in the studied territory is given. Inventory and certification of waste The GIS database on materials of researches is developed. The risk assessment for population health is given. Engineering-ecological and sanitary and epidemiologic actions for environment protection and public health care in the studied area are developed.